"You have to say everything is nice here": Complexities of gatekeeping in qualitative research in northern Mozambique. (21st May 2019) - Kalina, Marc; Scott, Dianne
Abstract : Purpose: The purpose of this paper is to reflect on the author's research experiences in northern Mozambique in order explore the multiplicity of gatekeeper relations that arose while seeking to arrange access to both "the field" and respondents, as well as the impacts that these relationships had on the research process. Although this dynamic has been thoroughly described within methodological literature, there exists a tendency to presume research–gatekeeper relations as static; once established, there is little discussion on how the relationships develop or can be managed, once access has (or has not) been achieved. Design/methodology/approach: The paper draws upon qualitative fieldwork conducted predominantly in rural communities in northern Mozambique. The study analysed the development of the Nacala Development Corridor programme and the N13 Highway Rehabilitation Project in northern Mozambique in order to examine the impacts of the development on local citizens and examine the relationship between citizen and state within development processes. Fieldwork consisted of three different phases of semi-structured and open-ended interviews with key stakeholders and affected persons, spanning five different interview schedules, and a total of 77 individual interviews and 27 community focus groups conducted along the N13. Findings: The study found that duality of Mozambican governance which includes both local officials and traditional leadership contributed to a multiplicity of local gatekeepers which impacted the research process in a multitude of ways. As a result, researcher–gatekeeper relations were not static, but had to be managed throughout the duration of the study. Originality/value: This discussion provides a more dynamic representation of the challenges involved with establishing and managing gatekeeper relations in rural, developing, and in particular, southern African, contexts, while offering cautious practical advice to researchers working within rural or southern African contexts.